Predicting a reduction in intraocular pressure in glaucoma patients in the early period after a trabeculectomy: Development and assessment of a new predictive nomogram - Wang, Ruixue; Li, Ning; Tan, Yue; Chen, Xiaoya (Frontiers in Ophthalmology, 2022)
Purpose: To identify the factors associated with a reduction in intraocular pressure (IOP) in the early postoperative period after a trabeculectomy and to develop a predictive nomogram to guide clinical care. Methods: This study included clinical data on 588 glaucoma patients (N = 588 eyes) who underwent a trabeculectomy in our hospital between January 2016 and December 2021. There were 412 eyes in a training cohort and 176 eyes in a validation cohort. We used logistic regression analysis to evaluate whether these factors were related to a decrease in IOP in the early period postsurgery and established a predictive model by combining features selected in a univariate analysis. We used external validation for evaluation. The standard for IOP reduction was that the IOP decreased to the normal range (10−21 mmHg) 1 month after the trabeculectomy. Results: Among the patients in the training cohort, 82.8% met the standard for IOP lowering. There were 11 meaningful differences among the enrolled predictors, but the logistic regression analysis only showed significant differences with anterior chamber angle closed, age, preoperative IOP, axial length, and visual field mean sensitivity (MS). The C-index of the model was 0.910 (95% confidence interval [CI]: 0.869-0.951). The C-index was 0.956 for external validation of the model. Conclusion: This new nomogram can be used to predict whether the IOP will reach the standard in the early stages after a trabeculectomy. The anterior chamber angle closed, age, preoperative IOP, axial length, and visual field MS are independent risk factors.